Microstructure-dependent mechanical behaviors of SiC nanowires - Wang, Jun; Lu, Chunsheng; Wang, Qi; Xiao, P.; Ke, F.; Bai, Y.; Shen, Y.; Liao, X.; Gao, H. (Nil, 2012)
The tensile behaviors of [111]-oriented SiC nanowires (NWs) with various microstructures are investigated by using molecular dynamics simulations. The results elucidate the influence of microstructures on brittleness and plasticity of SiC NWs. Plastic deformation is mainly induced by the anti-parallel sliding of 3C grains along an intergranular amorphous film parallel to the (111) plane and inclined at an angle of 19.47° with respect to the NW axis. Also revealed is that the wide dispersion of mechanical properties of SiC NWs observed in experiments is attributed to their diverse microstructures.